The effect of e-learning system quality on training engagement to improve creativity among workforce of public sector in the Ministry of Interior Abu Dhabi, United Arab Emirates (UAE) - Alkaabi, Ahmed Salem Saleh Sulaiman (2025)
Creativity development has become crucial in changing scenarios worldwide, especially in the changing nature of work requirements. The majority of governments worldwide stress the implementation of e-learning systems and continuously urge the improvement of the quality of e-learning. Furthermore, without engaging the learners, the success of any program will be difficult. Therefore, the purpose of the study is to identify the impact of e-learning system qualities on training engagement to improve creativity among the employees in the Ministry of Interior Abu-Dhabi, United Arab Emirates. The ministry was chosen due to the UAE's focus on employees’ creativity to cope with the economic downturn after the COVID-19 pandemic. Although the government invested a lot in e-learning system qualities, they were facing issues during the implementation of it. The investment theory of creativity has been used as the underpinning theory to develop the framework which has been tested over the data collected from 400 employees working at the Ministry of Interior Abu-Dhabi using the questionnaires adopted from prior studies. After ensuring the external model for checking the reliability of the data, the inner model was evaluated to test the hypothesis raised in the study. The findings revealed that all the direct and indirect hypotheses were accepted, confirming that e-learning system qualities significantly impacted employees’ creativity and training engagement mediates the relationship between the dimensions of e-learning system qualities (system quality, service quality, interface quality and emotional quality) and employees’ creativity. Theoretically, this study contributed to the use of the investment theory of creativity in studying the context of e-learning system qualities and training engagement in improving employees’ creativity. From a practical point of view, this study found that e-learning system quality and training engagement have great potential to enhance employees’ creativity in the UAE based on the factors studied